O poder normativo das agências reguladoras: deslegalização, legitimidade democrática e controle - Lima , Artur Carnauba Guerra Sangreman (2016)
First introduced in Brazil in the 1990s, the concept of regulatory agencies was aimed at adding specialization and technical knowledge to the government‟s decision-making process with regards to specific sectors of the economy and of public services. Based on a special legal framework, public authorities were thus created and granted administrative, technical decisional, normative, and political independence. The highlight is the normative capability of these regulatory agencies, which means they have the power to issue regulations that can bring innovation to the legal system. Yet, this regulatory normative power has been pelted with harsh criticism, of which the violation of the principle of legality and the lack of democratic legitimacy stand out. Contrariwise, it is necessary to assess the idea of juridicity, the phenomenon of delegalization, the characteristics of a participatory democracy, and the different systems of controlling government policy and action, all of which lend themselves to the strengthening of the legitimacy of their juridical and political acts